2021
DOI: 10.1038/s41467-021-26728-4
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol-boundary-layer-monsoon interactions amplify semi-direct effect of biomass smoke on low cloud formation in Southeast Asia

Abstract: Low clouds play a key role in the Earth-atmosphere energy balance and influence agricultural production and solar-power generation. Smoke aloft has been found to enhance marine stratocumulus through aerosol-cloud interactions, but its role in regions with strong human activities and complex monsoon circulation remains unclear. Here we show that biomass burning aerosols aloft strongly increase the low cloud coverage over both land and ocean in subtropical southeastern Asia. The degree of this enhancement and it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
55
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(57 citation statements)
references
References 72 publications
2
55
0
Order By: Relevance
“…PM 2.5 that is emitted by intense burning affects not only local air but also that of downwind regions through atmospheric transport (Li et al., 2019, 2021; Poulain et al., 2021; Wang et al., 2018). The impact of smoke transport has been well studied in regions with frequent fire activities, such as Central America (Saide et al., 2015; Wang & Christopher, 2006), Russia (Li et al., 2019; Mielonen et al., 2012; Péré et al., 2014), Africa (Ansmann et al., 2009; Williams et al., 2012), and South/Southeast Asia (Ding et al., 2021; Engling et al., 2011; Wang et al., 2017, 2021; Zhang et al., 2018; Zhu et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…PM 2.5 that is emitted by intense burning affects not only local air but also that of downwind regions through atmospheric transport (Li et al., 2019, 2021; Poulain et al., 2021; Wang et al., 2018). The impact of smoke transport has been well studied in regions with frequent fire activities, such as Central America (Saide et al., 2015; Wang & Christopher, 2006), Russia (Li et al., 2019; Mielonen et al., 2012; Péré et al., 2014), Africa (Ansmann et al., 2009; Williams et al., 2012), and South/Southeast Asia (Ding et al., 2021; Engling et al., 2011; Wang et al., 2017, 2021; Zhang et al., 2018; Zhu et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Peatland fires cause a broad suite of other impacts as well. The direct effect of aerosol emissions can offset GHG warming depending on their optical properties (Stockwell et al, 2016a;Eck et al, 2019;Pokhrel et al, 2016;Liu et al, 2014), and the aerosols also impact cloud cover (Ding et al, 2021) and rainfall (Hodzic and Duvel, 2018;Chen et al, 2017;Lu and Sokolik, 2013). The aerosols and gases emitted by Southeast Asian peatland fires are extensive enough to impact air quality regionally (Aouizerats et al, 2015;Hansen et al, 2019;Kiely et al, 2020;Koplitz et al, 2016;Tosca et al, 2011;Wooster et al, 2018;etc.).…”
Section: Introductionmentioning
confidence: 99%
“…The authors reported that BC particles were transported to the glaciers in the Tibetan Plateau, where it significantly affected the melting of the snow, causing some severe environmental problems, such as water resource depletion. Ding et al (2021) indicated that BB aloft aerosols strongly increase the low cloud coverage over both land and ocean and affect the monsoon in the subtropical Southeast Asia.…”
Section: Introductionmentioning
confidence: 99%